You need to realize that this expression means (2x+4)(2x+4). This is what the word 'squared' means. So, we have two binomials that are being multiplied.
This calls for the FOIL method! :)
FOIL = first, outer, inner, last
This is the order at which we need to multiply the binomials.
2x•2x = 4x^2
Then outer:2x•4 =8x
Then inner:4•2x = 8x
Then last: 4•4 = 16
So we have this expression: 4x^2+8x+8x+16
We need to combine like terms to simplify.
So, the above expression becomes
4x^2 + 16x +16
Easy right? :D Best of luck!